How long should we fear? Long-term risk of venous thromboembolism in patients with traumatic brain injury. Issue 1 (July 2016) - Olufajo, Olubode A.; Yorkgitis, Brian K.; Cooper, Zara; Rios-Diaz, Arturo; Metcalfe, David; Havens, Joaquim M.; Kelly, Edward; Haider, Adil H.; Gates, Jonathan D.; Salim, Ali
Abstract : BACKGROUND: Although patients with traumatic brain injury (TBI) are known to be at high risk for venous thromboembolism (VTE), it is not clear how long this risk persists after injury. We aimed to determine the risk of VTE in patients with TBI during one year after injury and to identify associated factors. METHODS: Patients 18 years and older with International Classification of Diseases, Ninth Revision, Clinical Modification diagnoses of isolated TBI (head Abbreviated Injury Scale [AIS] ≥3 and AIS <3 for all other body regions) were identified in the California State Inpatient Database (2007–2011). Patient and admission (injury severity score, length of stay, and discharge disposition) characteristics were assessed. Hospital factors (teaching status, trauma center verification, and bed size) were extracted from the American Hospital Association database. Patients who developed VTE during the index admission and at different time points after discharge were determined. Multivariate logistic regression models were used to assess the associated risk factors for VTE after discharge. RESULTS: There were 38, 984 patients with isolated TBI identified. The incidence of VTE was 1.31% during the index admission and the cumulative incidence of VTE involving hospitalization within one year of injury was 2.83%. The major risk factors for VTE one year after injury (not including the index admission) were discharge to extended care facilities versus home [adjusted odds ratio, 2.69 (95% confidence interval, 2.14–3.37)], age older than 64 years versus 18 to 44 years [2.62 (1.80–3.81)], having an operation during the index admission [1.65 (1.36–2.01)], and hospital length of stay of more than 7 days versus 3 days or less [1.64 (1.27–2.11)]. CONCLUSION: The risk of VTE persists long after discharge in a significant proportion of patients with TBI. Demographic and admission characteristics of patients play significant roles in the risk of VTE after discharge. These results highlight the need for sustained surveillance and preventive measures among patients with TBI at increased risk for long-term VTE. LEVEL OF EVIDENCE: Epidemiologic study, level III. Abstract : Supplemental digital content is available in the text.